MODELING OF THERMAL WATER STRATIFICATIOIN BEHAVIOR IN A SYSTEM WITH A MOBILE BOTTOM - Nosov M.A.; Ivanov P.S.; Shelkovnikov N.K. (My University, 1996)
Unusual hydrodynamic phenomena are often observed around the epicenters of underwater earthquakes; they are known as seaquakes. Physical modeling of disturbances in thermal stratification has been carried out for a hydrodynamic system with an oscillating lower boundary. Turbulent exchange coefficient K(z) was estimated at bottom oscillation frequencies corresponding to three different dynamic modes. It is shown that K(z) does not differ much from the molecular coefficient for frequencies of 1 to 10 Hz, at which ordinary linear waves are generated, whereas the transition (as the frequency increases) to structures appearing on the water surface and further chaotization modify the temperature profile and make K(z) two orders greater.